Beyond grades: developing knowledge sharing in learning communities as a graduate attribute. Issue 2 (23rd February 2019) - Brouwer, Jasperina; Jansen, Ellen
ABSTRACT: The ability to share knowledge is an important attribute that students develop in learning communities (LCs), enabling them to succeed in their education and careers. Insufficient research addresses the development of such knowledge sharing in LCs though, including whether it aligns with students' success (i.e., grades). To address this gap, the current study investigates various determinants of knowledge sharing and their effects on student success. Survey data from 183 psychology students measure altruism, trust, belongingness (community identification), perceived social interaction, and attitudes toward and expectations of the benefits of knowledge sharing. A path analysis shows that trust affects the expected personal and community benefits of knowledge sharing indirectly, through students' general attitudes toward knowledge sharing. Altruism, trust, and belongingness affect the personal benefits of knowledge sharing indirectly through social interaction. No significant relation emerges with first-year study success. Knowledge sharing as added attribute does not appear aligned with study success measured by individual course grades.